Measuring Regional Inequalities by Amenity Productivity Approach for Sustainable Economic and Environmental Policies in EU - Giannias, Dimitrious; Chepurko, Yuri; Figus, Alessandro; Hiá»ƒn, Nguyá»…n HoÃ ng (International Journal of Energy Economics and Policy, 2017)
This paper classifies the European Union (EU) member countries on an amenity-productivity map based on environmental quality and income differentials. This classification is useful because it provide information about the relative attractiveness to consumer and producers of the total bundle of such attributes indigenous to each region environmental and other. It also assists European policy makers to formulate the best suited regional and environmental policies in the EU. Our findings suggest that notion of sustainable development is best suited for low productivity countries such as Greece, Portugal, Spain, Ireland, and Italy. Keywords: Environmental quality and income inequalities, environmental policy, isocost, isoutility, regional policy, amenities, productivity JEL Classifications: Q5; Q50; R11; R58; Q56